2016
DOI: 10.11646/zootaxa.4066.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Limnodrilus sulphurensis n. sp., from a sulfur cave in Colorado, USA, with notes on the morphologically similar L. profundicola (Clitellata, Naididae, Tubificinae)

Abstract: A new species of the tubificine genus Limnodrilus is described and COI barcoded from Sulphur Cave and associated springs in Colorado, USA. The habitats are characterized by high sulfide concentrations. The new species, L. sulphurensis, is distinguished from all congeners by the elongate, nearly parallel teeth of chaetae in its anterior segments. It has a penis sheath resembling that of L. profundicola; consequently, museum specimens and new collections are examined here to resolve some of the taxonomic confusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…If we consider groups other than arthropods and vertebrates, we find that annelids have undergone several ecological radiations, correlated to dramatic morphological changes leading to overly simplistic, and to highly specialized body forms ranging from micro‐ to macroscopic (Rouse & Pleijel, ). Time and again, annelids have shown to be extremely successful in colonizing caves, with most recent discoveries showcasing their adaptive abilities in surviving even amidst sulphidic springs (Fend et al., ). In some cave systems, annelids represent the second most diverse group after crustaceans (arthropods; Martínez García, Palmero, Brito, Núñez, & Worsaae, ; Worsaae, Martínez, & Núñez, ).…”
Section: Introductionmentioning
confidence: 99%
“…If we consider groups other than arthropods and vertebrates, we find that annelids have undergone several ecological radiations, correlated to dramatic morphological changes leading to overly simplistic, and to highly specialized body forms ranging from micro‐ to macroscopic (Rouse & Pleijel, ). Time and again, annelids have shown to be extremely successful in colonizing caves, with most recent discoveries showcasing their adaptive abilities in surviving even amidst sulphidic springs (Fend et al., ). In some cave systems, annelids represent the second most diverse group after crustaceans (arthropods; Martínez García, Palmero, Brito, Núñez, & Worsaae, ; Worsaae, Martínez, & Núñez, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on ingestion rates and assimilation efficiencies under anoxia are contradictory. Volpers and Neumann (2005) suggested that worms stop feeding below 0.3 mg O2 l -1 , however some tubificid species can grow and feed actively despite severe hypoxia (down to 0.005 mg O2 l -1 ) and sulfide atmospheres (Fend et al 2016). Worm behavior in the field under temporal hypoxia or anoxia in the water column is unknown, which makes model predictions difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The new material has a relatively elongate atrium, probably more similar to Claparède's illustration than to the atria of some other species (e.g., Limnodrilus profundicola [cf. figure 4 in (Fend et al 2016)]). Penial musculature is often prominent in the genus, with a characteristic spiral arrangement in some worms that have been attributed to L. hoffmeisteri (Eisen 1885;Chen 1940;Moore 1905).…”
Section: Speciesmentioning
confidence: 99%
“…The neotype and associated specimens have a relatively elongate (tubular) spermathecal duct, compared with, e.g., L. profundicola (Cui et al 2015, fig. 7;Fend et al 2016).…”
Section: Speciesmentioning
confidence: 99%